Bis(4-amino-3,5-di-2-pyridyl-1,2,4-triazole-κ2N1,N5)diaquazinc(II) dinitrate - Jia Hua; Lu Gao; Baiyan Li (Acta Crystallographica Section E, 2009)
The asymmetric unit of the title compound, [Zn(C12H10N6)2(H2O)2](NO3)2, contains one-half of the complex molecule and one NO3− anion. The ZnII ion displays a distorted tetragonal-pyramidal geometry with four N atoms from two chelating 4-amino-3,5-di-2-pyridyl-1,2,4-triazole (2-bpt) ligands in the basal plane and one water molecule occupying the apical site. Another water molecule at the opposite of the apical site has a weak interaction with the ZnII ion [Zn—O = 2.852 (5) Å]. The ZnII ion and the two water molecules lie on a twofold rotation axis. An extensive system of hydrogen bonds involving the NH2 groups of the 2-bpt ligands, water molecules and nitrate anions links all residues into a three-dimensional network.